2000
DOI: 10.7326/0003-4819-133-6-200009190-00013
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Reactions in HIV-1–Infected Persons after Initiation of Highly Active Antiretroviral Therapy

Abstract: Clinicians caring for patients who are infected with HIV-1 and receiving HAART must be aware of this new and diverse clinical syndrome. As more HAART recipients are studied, new presentations will probably be observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
163
0
12

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(178 citation statements)
references
References 65 publications
3
163
0
12
Order By: Relevance
“…It represents a diagnostic challenge, with limited treatment options and variable prognosis. 61 The diagnosis of IRIS must be suspected when clinical symptoms are more consistent with an inflammatory process rather than an expected course of an opportunistic infection or drug toxicity. In the setting of HIV infection, risk is higher for antiretroviral naïve patients, but it is also related to the duration and extent of immunodeficiency, polymorphisms in cytokine genes, high initial viral load and rate of immune reconstitution.…”
Section: Irismentioning
confidence: 99%
“…It represents a diagnostic challenge, with limited treatment options and variable prognosis. 61 The diagnosis of IRIS must be suspected when clinical symptoms are more consistent with an inflammatory process rather than an expected course of an opportunistic infection or drug toxicity. In the setting of HIV infection, risk is higher for antiretroviral naïve patients, but it is also related to the duration and extent of immunodeficiency, polymorphisms in cytokine genes, high initial viral load and rate of immune reconstitution.…”
Section: Irismentioning
confidence: 99%
“…The diagnosis is often challenging, treatment options are limited, and the prognosis is variable. 61 The diagnosis of IRIS is advocated when a patient meets the following criteria 62 : known HIV-positive patient receiving HAART with a decrease in the HIV-1 ribonucleic acid level from baseline and an increase in CD4ϩ cells from baseline with clinical symptoms consistent with an inflammatory process rather than an expected course of previously diagnosed opportunistic infection or the expected course of newly diagnosed opportunistic infection or drug toxicity. In the CNS context, the disease may be called NIRIS.…”
Section: Iris and Nirismentioning
confidence: 99%
“…Mortality could be further avoided by monitoring those with advanced disease as they start ART, and it raises the possibility that early mortality could also be due to undiagnosed opportunistic infections, nutritional deficiencies, or severe immune reconstitution inflammatory syndrome, although there is no direct evidence to support these possible reasons. [23][24][25] This study showed reduced early mortality as patients who attended the clinic were diagnosed quickly and were counselled to start ART before they become wasted and anemic. 6 Though the stigma associated with the disease prevent patients from seeking early treatment, the free provision of drugs by government ART centres has encouraged people to seek medical attention earlier, as has been observed in the United States and other developed countries.…”
Section: Discussionmentioning
confidence: 99%